P-E4 The MoMent Study: Correlates of viral suppression at 6 months postpartum among HIV-positive women in rural Nigeria. (April 2018) - Ramadhani, Habib; Isah, Christopher; Charurat, Manhattan; Sam-Agudu, Nadia
Abstract : Introduction: The risk of mother-to-child transmission of HIV (MTCT) reduces with sustained pre & postpartum administration of suppressive maternal ARVs. The MoMent study evaluated for maternal viral suppression & its correlates among HIV+ Nigerian women. Methods: This prospective cohort study compared structured Mentor Mother (MM) vs unstructured peer support (PS) for PMTCT outcomes. Pregnant women were recruited at 20 matched Primary Healthcare Centers in rural North-Central Nigeria. Structured PS included daily MM supervision, standardized documentation, client tracking, & MM performance evaluations. Maternal viral load (VL) was performed at 6 months postpartum; women lost to followup were tracked back for VL tests. Viral suppression was defined as VL <20 copies/mL. All participants were on ART for ≥6 months. Multivariate logistic regression with generalized estimating equations was used to account for clusters and for adjusting confounders. Results: Among 497 enrolees, 296 (59.6%) presented for VL; 273/296 (92.2%) had samples collected. Of the 238/273 (87.2%) with available results, 138 (58%) were suppressed. Correlates of suppression were structured MM support (aOR 4.9, CI 2.6 to 9.2); age >30 years (aOR 2.3, CI 1.0 to 4.9); ≥secondary education (aOR 2.0, CI 1.2 to 3.3); Christian religion (aOR 1.4, CI 1.1 to 2.1); PI-based ART (aOR 4.6, CI 1.3 to 16.0), and retention (aOR 3.7, CI 2.5 to 5.5). Marital/disclosure status & distance from facility were not significant. Discussion: Organized PS, older age, education, potent ARVs & retention supported viral suppression in our study. The role of religion is unclear & should be further explored. Conclusion: Structured PS should be targeted to young & lesser educated women to reduce MTCT risk.